On-farm phenotypic characterization of Sheko breed of cattle and their habitat in Bench Maji zone, Ethiopia - Teye, T. (2005)
This study was initiated in response to the national concern emerged on the current status of the distinctive, however, endangered Brachyceros group of cattle, Sheko breed, for effective utilization in food and agriculture production. The objectives of the study were: 1) to undertake on-farm phenotypic characterization of Sheko breed of cattle in their natural habitat; 2) to assess the population trend; 3) to assess trait and breed preferences of the community and 4) to document some husbandry practices and constraints in utilization of the breed. The field study was carried out in Bench Maji Zone, southwestern Ethiopia, which is the main natural breeding tract of Sheko cattle. Purposive sampling was employed as sampling technique. Semi-structured interviews, focus group discussions, field observations of animals and secondary data collection were employed to generate the data. Statistical Analysis System software was employed to analyze the data. The geographical distribution of Sheko cattle is generally restricted mainly to Bench Maji Zone and partly in the adjoining parts of Kaffa and Shaka Zones. The current population of Sheko cattle is estimated to be about 4040, which is far less compared to the previous estimates. This indicates that the Sheko cattle population is decreasing. The identified main threats to the survival of Sheko cattle were interbreeding with Zebu cattle, scarcity of feed resources and shrinkage of grazing land, lack of conservation program, lack of reliable information on the actual status of the breed and lack of interest by the community owing to the aggressive behavior of this breed. Sheko cattle do have specific morphological appearance, which can be utilized in identifying this breed. Polledness is common in Sheko cattle. They are generally short and have compact body. Their eyes are prominent and have folded eyelid. They have broad and short horizontally oriented ears. Their muzzle is broad and their facial profile is predominantly straight. They are alert and strong. They have small cervico-thoracic hump. The coat color is dominated by red with glossy appearance. The average linear body measurement taken on a total of 167 female animals for chest girth, body length, height at withers and pelvic width was 136.5, 110.2, 99.4 and 33.5cm respectively, averages of these variables for 46 males were 141.2, 114.6, 103.6 and 32.8 cm, respectively. The reported average age at maturity in male and female Sheko cattle were 41.6 and 42.1 months, respectively and the associated average age at first calving was 54.1 months. The average reproductive lifespan of a cow was reported to be 14.7 years with a total average calf-crop of 8.3. The mean calving interval was reported to be 15.6 months. Bulls were said to have average reproductive lifespan of 6.5 years. The males were castrated at an average age of 5.7 years. The reported average lactation milk yield was 698.3 liters with average lactation length of 9.9 months, with significant differences in lactation yield between herds in the Shei Bench with both Sheko and Bench districts. The Sheko ox on average starts ploughing at the age of 3.4 years with average work life of 8.5 years. In terms of breed preferences, 43.2 percent of the respondents made Sheko their breed of choice, and milk production was the most frequently (49.6%) preferred trait, followed by breeding efficiency (20.8%). In spite of these special qualities the breed is under serious threat and hence an integrated and community driven participatory in-situ and ex-situ conservation and genetic improvement program of the Sheko breed is proposed to reverse the present genetic erosion of the breed, which otherwise threatens its mere existence.